2017
DOI: 10.1111/dar.12524
|View full text |Cite
|
Sign up to set email alerts
|

Latent classes of polydrug and polyroute use and associations with human immunodeficiency virus risk behaviours and overdose among people who inject drugs in Tijuana, Baja California, Mexico

Abstract: Introduction and Aims. Patterns of polydrug use among people who inject drugs (PWID) may be differentially associated with overdose and unique human immunodeficiency virus (HIV) risk factors. Subgroups of PWID in Tijuana, Mexico, were identified based on substances used, route of administration, frequency of use and co-injection indicators. Design and Methods. Participants were PWID residing in Tijuana age ≥18 years sampled from 2011 to 2012 who reported injecting an illicit substance in the past month (n = 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
(49 reference statements)
3
30
0
Order By: Relevance
“…Fourth, this study focused on the specific effects of the use of individual drugs by non-injection. We note that a study conducted recently by Meacham and colleagues in the same setting suggested that poly-drug and poly-route users may represent specific subgroups with an increased risk of engaging in HIV risk behaviors [48]. This may underline the need for future research studies to assess whether these subgroups are at greater risk of providing injection initiation assistance.…”
Section: Discussionmentioning
confidence: 82%
“…Fourth, this study focused on the specific effects of the use of individual drugs by non-injection. We note that a study conducted recently by Meacham and colleagues in the same setting suggested that poly-drug and poly-route users may represent specific subgroups with an increased risk of engaging in HIV risk behaviors [48]. This may underline the need for future research studies to assess whether these subgroups are at greater risk of providing injection initiation assistance.…”
Section: Discussionmentioning
confidence: 82%
“…However, our results in terms of proportions of overdoses averted should be robust to uncertainty in the absolute overdose rate. Fourth, we neglected polysubstance use, but 15% of PWID in Tijuana report injecting both opioids and stimulants, which could alter the effect of opioid agonist therapy [53]. We purposely limited opioid agonist therapy scale-up to 40% coverage among PWID to account for a proportion who may be ineligible.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 More recently, person-centered approaches such as latent class analysis (LCA) and latent profile analysis (LPA) have emerged in the literature. 19,[33][34][35][36][37] However, most of the studies that examine patterns of polydrug use limited the scope of the types of substances included (e.g., drinking behaviors, injection drugs, illicit drugs), with specific foci on different subpopulations, such as adolescents, people who inject drugs, chronic pain patients, etc.…”
Section: Rationale and Significance Of The Studymentioning
confidence: 99%
“…Four major criteria were used to decide which substance use variables went into the LCA model: type of substance, route of administration, co-injection, and frequency of use. 33 From the LCA analysis, participants were classified into five subgroups 33 Additionally, the investigators found that the two polydrug and polyroute classes (i.e., Classes 1 and 2) were more likely to report HIV risk behaviors (e.g., unprotected sex, having two or more sexual partners, drug use before or during sex, etc.) when compared to those who predominantly injected heroin (i.e., Class 5).…”
Section: Opioid-related Polydrug Use In People Who Inject Drugs (Pwid)mentioning
confidence: 99%
See 1 more Smart Citation